1980
DOI: 10.1051/rphysap:01980001505096100
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of bismuth films and its consequences on their electrical properties

Abstract: 2014 Les auteurs étudient les propriétés structurales des couches minces de bismuth à 1'aide des techniques suivantes : diffraction des électrons par réftexion, diffraction des rayons X, microscopie électronique par balayage et diffraction et microscopie électronique par transmission. Ils rappellent les propriétés électriques des couches minces de bismuth (mesures de conductivité et du facteur RH). Il apparait que les états de surface jouent un rôle déterminant dans les définitions des propriétés du facteur RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 23 publications
2
2
0
1
Order By: Relevance
“…As a result, the PF enhancement and hence higher ZT was observed in the sample ball‐milled in inert atmosphere (Bi‐bm60‐inert (Ar) atm) as compared to those ball‐milled in ambient atmospheric conditions (Bi‐bm60‐atm) with same SPS conditions. This is consistent with the previous reports depicting the effect of preparation conditions on surface transport in Bi thin films,28 and hence our results further confirm surface modifications as the most probable cause for observed enhancement in TE properties.…”
Section: Methodssupporting
confidence: 93%
“…As a result, the PF enhancement and hence higher ZT was observed in the sample ball‐milled in inert atmosphere (Bi‐bm60‐inert (Ar) atm) as compared to those ball‐milled in ambient atmospheric conditions (Bi‐bm60‐atm) with same SPS conditions. This is consistent with the previous reports depicting the effect of preparation conditions on surface transport in Bi thin films,28 and hence our results further confirm surface modifications as the most probable cause for observed enhancement in TE properties.…”
Section: Methodssupporting
confidence: 93%
“…Thus the change of sign in the Hall coefficient of Bi probes is not surprising and indeed has been noticed earlier by several authors [12,13,14,15,16].…”
Section: Methodssupporting
confidence: 81%
“…and V = (D/λ os )[ln(1/p -)] (11) where D is the grain diameter that it determined from x-ray (D=87.31 nm and d=120 nm). U and V were calculated and are listed in Table (2) with the other available data for comparison.…”
Section: Specular Scatteringmentioning
confidence: 99%
“…Bi-Sb is an efficient thermoelectric material at low temperature [3,4,6].The constituents of Bi 0.99 Sb 0.01 thin films have been the subject of many studies since it is regarded as one of the constituent materials of many binary and ternary compounds used in electronic devices. Previous studies [7][8][9][10][11][12] revealed that Bi-Sb thin film form crystallized in the hexagonal system and they also found that, the mean grain size increased with increasing the film thickness and decreased with Sb content. Many studies [7,[12][13][14][15][16] revealed that with decreasing film thickness, the resistance increases regularly, though as the thickness reaches certain magnitude, ρ starts to drop manifesting an anomalous size effect.…”
Section: Introductionmentioning
confidence: 99%